Story creation and the impact of travel journalists on destination brands - Freire, João (2021)
The main objective of this article is to present an insight into the process of story creation in the travel section of British newspapers. The research presented focuses on this specific area of written press in order to understand how stories are created and how destination brand managers can use and control this source of information to build brand image. In order to understand how journalists create their stories the authors conducted a qualitative research with six travel journalists. Because of the exploratory nature of this research, it was decided that the best method of data collection was in-depth interviews. Although the aim of the travel section is to inform readers, the nature of its written stories differs from the newspaper’s other articles. In fact, reports published in the travel section tend to be positive and boast an optimistic outlook about places and leisure activities. Two main reasons may explain why this happens: first, the reason why a person reads the travel section; second, the symbiotic relationship between the press and travel or leisure organisations. These aspects influence the nature of the published stories and impact on how journalists write their articles. Despite the relevance of travel journalism, research on the topic is scant. The process of creating a story is poorly understood and therefore difficult for DMOs to manage this source of image creation